Rehabilitation of Individuals With Diabetes Mellitus: Focus on Diabetic Myopathy - Bassi-Dibai, Daniela; Santos-de-Araújo, Aldair Darlan; Dibai-Filho, Almir Vieira; de Azevedo, Lisiane Fernanda Simeão; Goulart, Cássia da Luz; Luz, Gabriela Costa Pontes; Burke, Patrick Rademaker; Garcia-Araújo, Adriana Sanches; Borghi-Silva, Audrey (Frontiers in Endocrinology, 2022)
Diabetes mellitus (DM) is a chronic metabolic disease characterized by high blood glucose levels, causing serious damage to the cardiovascular, respiratory, renal and other systems over time. The prevalence of type 2 diabetes mellitus (T2DM) was 6.28% in 2017, considering all age groups worldwide (prevalence rate of 6,059 cases per 100,000), and its global prevalence is projected to increase to 7,079 cases per 100,000 by 2030. Furthermore, these individuals are often affected by diabetic myopathy, which is the failure to preserve muscle mass and function in the course of DM. This happens in type 1 diabetes mellitus and T2DM. As skeletal muscle plays a key role in locomotion and glucose homeostasis, diabetic myopathy may contribute to additional complications of the disease. In addition, chronic hyperglycemia is associated with lung functional changes seen in patients with DM, such as reduced lung volumes and compliance, inspiratory muscle strength, and lung elastic recoil. Thus, the weakness of the inspiratory muscles, a consequence of diabetic myopathy, can influence exercise tolerance. Thus, moderate strength training in T2DM can contribute to the gain of peripheral muscle strength. Although the literature is robust on the loss of mass and consequent muscle weakness in diabetic myopathy, triggering pathophysiological factors, the impact on functional capacity, as well as the prescription of physical exercise for this condition deserves to be further explored. This review aims to explore the consequences of diabetic myopathy and its implication in rehabilitation from prescription to safety in the practice of physical exercises for these individuals.